2013
DOI: 10.1371/journal.pone.0074803
|View full text |Cite
|
Sign up to set email alerts
|

Combining Phylogenetic and Syntenic Analyses for Understanding the Evolution of TCP ECE Genes in Eudicots

Abstract: TCP ECE genes encode transcription factors which have received much attention for their repeated recruitment in the control of floral symmetry in core eudicots, and more recently in monocots. Major duplications of TCP ECE genes have been described in core eudicots, but the evolutionary history of this gene family is unknown in basal eudicots. Reconstructing the phylogeny of ECE genes in basal eudicots will help set a framework for understanding the functional evolution of these genes. TCP ECE genes were sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 87 publications
1
34
0
Order By: Relevance
“…Our analysis also recovers the previously identified duplication of CYC-like genes in basal eudicots (Citerne et al, 2013), and another in Poales, the latter resulting in the REP1/TB1 clades (Mondragón-Palomino and Trontin, 2011). Most basal angiosperms and many monocots outside Poales have single copy CYC-like genes that predate the independent duplications in eudicots and Poales (Figure 1).…”
Section: Resultssupporting
confidence: 87%
“…Our analysis also recovers the previously identified duplication of CYC-like genes in basal eudicots (Citerne et al, 2013), and another in Poales, the latter resulting in the REP1/TB1 clades (Mondragón-Palomino and Trontin, 2011). Most basal angiosperms and many monocots outside Poales have single copy CYC-like genes that predate the independent duplications in eudicots and Poales (Figure 1).…”
Section: Resultssupporting
confidence: 87%
“…Studies in Poaceae, Zingiberales and Commelinales also suggest a possible role of T b 1-like genes, the closest C yc paralog in monocots, in the independent evolution of floral bilateral symmetry [16], [23], [24]. In parallel with the situation observed in core eudicots and monocots, independent duplications of C yc -like genes have been observed in all major lineages of basal eudicots, including the Ranunculales [25]. Studies in Fumarioideae (Papaveraceae) species showed that late expression of the two C yc -like genes was correlated with symmetry type [26], [27].…”
Section: Introductionmentioning
confidence: 80%
“…The phylogenetic analysis with all newly isolated CYCL genes recovers, although with low support, the three core eudicot subclades CYC1 ( TCP18 ), CYC2 ( TCP1 ) and CYC3 ( TCP12 ), that have been previously reported (Howarth and Donoghue, ; Citerne et al ., ), likely resulting from two consecutive duplications coincident with whole genome duplications known to have occurred with the diversification of the core eudicots (Jiao et al ., ). Relationships between the subclades are unclear as there is not sufficient resolution in these nodes (Figure S1).…”
Section: Resultsmentioning
confidence: 99%